Safety considerations in the treatment with anti-CGRP(R) monoclonal antibodies in patients with migraine - Van Der Arend, Britt W. H.; Van Veelen, Nancy; De Ruijter, Joëlle E. T.; Olsen, Michael H.; MaassenVanDenBrink, Antoinette; Terwindt, Gisela M. (Frontiers in Neurology, 2024)
Background: Anti-CGRP-(receptor-)monoclonal antibodies (anti-CGRP(R)-mAbs) represent a novel class of drugs for migraine treatment, but their long-term cerebrovascular and cardiovascular (CV) safety warrants further examination.In this observational cohort study we assessed the CV safety for erenumab and fremanezumab in a real-world setting during a follow-up period of at least one year. Patients with hypertension or CV history were excluded. We conducted ECGs and collected clinical data at treatment initiation and thereafter every three months, including liver and kidney function, lipid-, electrolyteand glucose levels.Results: Among patients receiving erenumab (n=101) or fremanezumab (n=92), 3.1% (6/193) developed abnormal ECGs or CV adverse events. Of these, three (1.6%) experienced moderate to severe CV adverse events (cerebellar stroke, spontaneous coronary artery dissection, and pericarditis) and discontinued treatment. The remaining three (1.6%) developed non-threatening ECG abnormalities without physical complaints. No significant changes were observed in liver and kidney function, lipid-, electrolyte-, or glucose levels.We observed CV events in 1.6% of patients with 1.5-year follow-up of anti-CGRP(R)-mAbs treatment. We advise awareness regarding CV events in patients with migraine undergoing CGRPtargeted treatment, not as a confirmation of increased risk but as a proactive measure to address potential multifactorial influences.